Independent assessment of source position for gynecological applicator in high-dose-rate brachytherapy - Okamoto, Hiroyuki; Nakamura, Satoshi; Nishioka, Shie; Iijima, Kotaro; Wakita, Akihisa; Abe, Yukinao; Tohyama, Naoki; Kawamura, Shinji; Minemura, Toshiyuki; Itami, Jun (Journal of Contemporary Brachytherapy, 2017)
Purpose : The aim of this study is to describe a phantom designed for independent examination of a source position in brachytherapy that is suitable for inclusion in an external auditing program. Material and methods : We developed a phantom that has a special design and a simple mechanism, capable of firmly fixing a radiochromic film and tandem-ovoid applicators to assess discrepancies in source positions between the measurements and treatment planning system (TPS). Three tests were conducted: 1) reproducibility of the source positions (n = 5); 2) source movements inside the applicator tube; 3) changing source position by changing curvature of the transfer tubes. In addition, as a trial study, the phantom was mailed to 12 institutions, and 23 trial data sets were examined. The source displacement ΔX and ΔY (reference = TPS) were expressed according to the coordinates, in which the positive direction on the X-axis corresponds to the external side of the applicator perpendicular to source transfer direction Y-axis. Results : Test 1: The 1σ fell within 1 mm irrespective of the dwell positions. Test 2: ΔX were greater around the tip of the applicator owing to the source cable. Test 3: All of the source position changes fell within 1 mm. For postal audit, the mean and 1.96σ in ΔX were 0.8 and 0.8 mm, respectively. Almost all data were located within a positive region along the X-axis due to the source cable. The mean and 1.96σ in ΔY were 0.3 and 1.6 mm, respectively. The variance in ΔY was greater than that in ΔX, and large uncertainties exist in the determination of the first dwell position. The 95% confidence limit was 2.1 mm. Conclusions : In HDR brachytherapy, an effectiveness of independent source position assessment could be demonstrated. The 95% confidence limit was 2.1 mm for a tandem-ovoids applicator.